The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fnagi.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

Promising Metabolite Profiles in the Plasma and CSF of Early Clinical Parkinson's Disease

Abstract: Parkinson's disease (PD) shows high heterogeneity with regard to the underlying molecular pathogenesis involving multiple pathways and mechanisms. Diagnosis is still challenging and rests entirely on clinical features. Thus, there is an urgent need for robust diagnostic biofluid markers. Untargeted metabolomics allows establishing low-molecular compound biomarkers in a wide range of complex diseases by the measurement of various molecular classes in biofluids such as blood plasma, serum, and cerebrospinal flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 108 publications
3
48
0
Order By: Relevance
“…Studies of cerebrospinal fluid (CSF) from patients with PD have identified PD-specific alterations in several metabolic pathways, including polyamine metabolism, the purine, pyruvate, kynurenine pathways, and redox markers (31,(33)(34)(35)(36). Although there is growing interest in the use of metabolomics in PD research, many of these studies do not corroborate each other possibly due to low sample numbers, clinical heterogeneity, and different analytical approaches (30).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of cerebrospinal fluid (CSF) from patients with PD have identified PD-specific alterations in several metabolic pathways, including polyamine metabolism, the purine, pyruvate, kynurenine pathways, and redox markers (31,(33)(34)(35)(36). Although there is growing interest in the use of metabolomics in PD research, many of these studies do not corroborate each other possibly due to low sample numbers, clinical heterogeneity, and different analytical approaches (30).…”
Section: Introductionmentioning
confidence: 99%
“…PD patients might suffer from dysfunction of the transport of neutral and basic amino acids across the blood-brain barriers (85). Changes in amino acid metabolism in plasma/CSF of the patients, highlighting the role of altered amino acid metabolism and PD pathology (86). Decreased amino acid concentrations could be involved in loss of microbial proteases/peptide catabolism (80).…”
Section: Dysregulation Of Metabolites and Neurodegenerationmentioning
confidence: 99%
“…Apart from the CAG repeat length, environmental and genetic modifiers might contribute to SCA7 pathophysiology [8]; thus, identification of sensitive biomarkers will facilitate the monitoring of disease progression and assessing of treatments, which ultimately will improve clinical management of patients. Metabolomics has emerged as a powerful technique to identify potential biomarkers in neurodegenerative diseases [19][20][21] as alterations in brain function can be reflected in the metabolite composition of biofluids such as the serum, plasma, and cerebrospinal fluid (CSF) [22][23][24]. Indeed, recent reports have described the detection of some neurometabolites associated with specific changes in neuronal and astrocytic cells in patients with different SCAs [25].…”
Section: Introductionmentioning
confidence: 99%